Development of the 3-phase 4-wire voltage sag generator - K. Oranpiroj (2018)
This paper presents development of 3-phase 4-wire voltage sag generator. Voltage sag generator is based on 3-phase 4-wire inverter in order to handle the neutral current caused by the unbalance and non-linear load. The controller used for this voltage sag generator is a low-cost dsPIC microcontroller. The 3 kVA voltage sag generator has been implemented. The paper also describes software to simulate and create controlled signal for generator. Software allows the user to directly program the voltage sag waveform by selecting the sag magnitude, sag duration, phase shift and voltage sag type. The simulation and experimental results have shown that this voltage sag generator can generate voltage sag in any conditions. © 2011 Academic Journals.